PENGARUH PERPUTARAN PIUTANG DAN KAS TERHADAP LIKUIDITAS PADA HILTON GARDEN INN BALI - RESTU DWI ROSALINA; COKORDA GEDE PUTRA YUDISTIRA; KADEK ENI MARHAENI; KASIANI KASIANI (Universitas Mahasaraswati K. Mataram, 2022)
Liquidity is an important factor for a company, especially in its long-term business. Healthy and ideal accounts receivable turnover and cash turnover are expected to help the company to achieve a good level of liquidity. This study aims to determine the effect of accounts receivable turnover and cash turnover on liquidity at the Hilton Garden Inn Bali, both partially and simultaneously. The data used in this study are secondary data, by collecting Hilton Garden Inn Bali's monthly financial statements consisting of balance sheet and income statements from January 2017 to December 2019. The amount of data used is 36 data. Data analysis techniques used in this study are calculating the value of each variable, the classic assumption test, multiple linear regression analysis, hypothesis testing, correlation analysis, and the coefficient of determination. The data analysis technique used SPSS version 24. The statistical test results showed that accounts receivable turnover had a significant positive effect on liquidity (current ratio), whereas cash turnover did not have a significant positive effect on liquidity (current ratio). Simultaneous accounts receivable turnover and cash turnover are not significant to liquidity (current ratio). Accounts receivable turnover and cash turnover affect liquidity by 15% while the remaining 85% is influenced by other variables not included in this study